Comparative study on the cost of hybrid energy and energy storage systems in remote rural communities near Yucatan, Mexico. (15th February 2022) - Buenfil Román, V.; Espadas Baños, G.A.; Quej Solís, C.A.; Flota-Bañuelos, M.I.; Rivero, M.; Escalante Soberanis, M.A.
Abstract: Many rural communities in developing countries rely on diesel-fueled power generation, in which the use of hybrid renewable energy systems (HRES) is an environmentally and economically attractive option. The main objective of this study is to analyze the feasibility to implement a HRES based on photovoltaic technology. The main contribution is to present a reliable and adaptable methodology to optimize an energy system sizing and fuel consumption to meet the power demand in rural areas, regardless of the geographic location or load profile, that can be easily implemented in freely available tools. For this purpose, a typical load scenario provided by an industrial partner is considered. This consumption data was compiled from experimental measurements in different rural communities, which averages a daily consumption of approximately 300 kWh. Three different power systems are analyzed: (i) a diesel generator with battery storage, (ii) a photovoltaic system with storage, and (iii) a photovoltaic system with diesel generator and battery storage. For each case, three storage technologies were considered, namely: lead–acid, Li-ion and absorbent glass mat (AGM), from which the first one was the least expensive. These storage systems were operated within the limits of maximum load and minimum discharge that each technology establishes. The photovoltaic/diesel-generator/AGM battery hybrid power system turned out to be the least expensive and the most feasible, with a net present cost of USD311, 632.53 and a cost of energy (COE) of USD0.14/kWh. The presented results demonstrate the advantages and disadvantages of each system, as well as their economic and technical feasibility. A cost reduction was found regarding the COE when comparing the system proposed in this study to other reported studies. Additionally, a sensitivity analysis was performed to report the impact of cost variations on the overall COE. These results prove that it is possible to satisfy the electrical demand of rural communities at a reasonable and accessible cost. Highlights: Spreadsheet-based optimization model developed for rural hybrid systems. Battery SOC was the main decision-making variable. Renewable energy penetration still relies on hydrocarbon fuels. A minimum COE of USD0.14/kWh was calculated for the optimized system. A sensitivity analysis delivered the capital cost of the PVS as the most relevant.